1999
DOI: 10.1080/02626669909492221
|View full text |Cite
|
Sign up to set email alerts
|

GR3J: a daily watershed model with three free parameters

Abstract: This paper describes a new empirical watershed model, the prime feature of which is its parsimony. It involves only three free parameters, a characteristic unparalleled by continuous process models able to work on a wide array of catchments. In spite of its crude simplicity, it achieved, on average, worthwhile results on a set of 140 French catchments and overwhelmingly outperformed a linear model involving 16 parameters. It performed roughly as well as a conceptual model with five free parameters, derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(131 citation statements)
references
References 11 publications
1
122
0
8
Order By: Relevance
“…Model parameters were calibrated by the automatic steepest descent optimization procedure used by Edijatno et al (1999). Several studies (Nascimento, 1995;Perrin, 2000;Mathevet, 2005) showed that this optimization method gives satisfactory results for models with up to ten free parameters, provided that the starting point of calibration is well-chosen in the parameter space.…”
Section: Methodsmentioning
confidence: 99%
“…Model parameters were calibrated by the automatic steepest descent optimization procedure used by Edijatno et al (1999). Several studies (Nascimento, 1995;Perrin, 2000;Mathevet, 2005) showed that this optimization method gives satisfactory results for models with up to ten free parameters, provided that the starting point of calibration is well-chosen in the parameter space.…”
Section: Methodsmentioning
confidence: 99%
“…The selected optimization technique is the steepest descent method summarized in Edijatno et al (1999). For distributed approaches we do not calibrate the parameters for each pixel (i).…”
Section: Impact On Model Calibrationmentioning
confidence: 99%
“…Pour la modalisation hydrologique déterministe, une variété beaucoup plus grande d'échelles d'études est couramment utilisée. En ingénierie, les modèles les plus populaires sont de type globaux : HBV (Bergström, 1995 ;Lindström et al, 1997), GR3J (Edijatno et al, 1999), UBC (Micovic et Quick, 1999)… Cependant, lorsque le bassin étudié comprend une large gamme d'altitudes et est affecté par des précipitations neigeuses significatives, un découpage en bandes d'altitude est souvent préféré (Kokkonen et al, 2001). Deplus, quand une description réellement physique de l'ensemble des processus élémentaires est entreprise, une discrétisation complète sur grille tridimensionnelle est nécessaire (Abbott et al, 1986).…”
Section: Par Rapport Aux Approches Déterministes De Type Modèles Hydrunclassified